Stalingrad [videorecording (DVD)] - Tilkin, Ilya; Snezhkin, Sergeĭ, 1954-; Smolʹnikova, Marii͡a, 1987-; Studilina, I͡Anina, 1985-; Fedorov, Petr, 1982- (Sony Pictures Home Entertainment, 2014)
An epic look at the battle that turned the tide of World War II. A band of determined Russian soldiers fight to hold a strategic building in their devastated city against a ruthless German army, and in the process become deeply connected to two Russian women who have been living there. The scale of the battle contrasts dramatically with the human drama of the Russian soldiers, the few remaining civilians and their invaders into Stalingrad.